Pengaruh Produk, Harga Dan Iklan Terhadap Keputusan Pembelian Pada Pasta Gigi Pbpsodent Di Surabaya Timur - Lilik Indrawati (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2011)
Nowadays, people are getting aware of the importance of keeping mouth and teeth healthy. One of the products which offer dental care is toothpaste which comes in many different brands. To understand better what their consumer want, therefore the producers of toothpaste make use the consumer behavior study so that their product is acceptable by their consumers. Toothpaste was first produced by Dresden Chemical Laboratory Lingner, which is now known as Lingner Werke AG in Germany in 1892. Back then toothpaste came in the form of mouthwash liquid. The most famous toothpaste in 1900 is